The determinants of citizens' preference of policy instruments for environmental policy: do social trust, government capacity, and state-society relations matter?. (3rd July 2019) - Cho, Beomgeun; Moon, M. Jae
ABSTRACT: This study aims to investigate the determinants of citizens' preferences for policy instruments. In particular, this study examines the impacts of social trust, government capacity, and the state-society relationship on citizens' preferences for policy instruments. To test the relationships among those variables, the study utilizes data from the ISSP (International Social Survey Program) Environmental III 2010, which includes 32 countries. The results show that regardless of policy target groups, social trust makes citizens prefer market-based policy instruments most, and a high level of government capacity leads citizens to favor indirect policy instruments over regulation. The influence of the state-society relationship is contingent on the social construction of the policy target groups except in the case of East Asian countries, which have a strong preference for suasive policy instruments.